Response of wheat to irrigation in a "cerrado" soil - Espinoza, Waldo; Silva, Eusebio M. da; Souza, Osni C. de (Pesquisa Agropecuaria Brasileira, 2014)
To evaluate the response of wheat to four water regimes in a Dark-Red Latosol, three native cultivars (IAS-55, BH-1146, IAC-5) and two introduced (Sonora-63 and Tanori/F-71) were irrigated when soil water tension reached 0.35; 0.70; 2.0 and 8.0 bars. The results indicate that as soil water tension (pF) increased, leaf area index (LAI) decreased (LAI = 15.62 exp. 0.64 pF). Leaf water potential was always higher in the native cultivars, confirming that they are better adapted to "Cerrado" soil conditions. Root development of the cultivars was not influenced by soil water tension, being restricted to the upper 20 cm of the soil, suggesting the presence of a limiting factor, presumably toxic aluminum. Daily evapotranspiration values, at flowering, were higher for the native cultivars more resistant to water stress (Y = 7.059 - 1.613,2 pF). Higher yields were obtained with frequent and low volume irrigations, applied every three to five days during the period of crop maximum demand being BH-1146 and IAC-5 the best cultivars. Water use efficiency (grain yield/evapotranspiration) (kg/mm) ranged from 11 to 13 for all of the cultivars, at the 0.35 bar tension treatment and from 3.5 to 5.0 for the 8.0 bars tension treatment.